If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 36 = 10x + -41 Reorder the terms: 36 + 3x = 10x + -41 Reorder the terms: 36 + 3x = -41 + 10x Solving 36 + 3x = -41 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. 36 + 3x + -10x = -41 + 10x + -10x Combine like terms: 3x + -10x = -7x 36 + -7x = -41 + 10x + -10x Combine like terms: 10x + -10x = 0 36 + -7x = -41 + 0 36 + -7x = -41 Add '-36' to each side of the equation. 36 + -36 + -7x = -41 + -36 Combine like terms: 36 + -36 = 0 0 + -7x = -41 + -36 -7x = -41 + -36 Combine like terms: -41 + -36 = -77 -7x = -77 Divide each side by '-7'. x = 11 Simplifying x = 11
| -2*2+((-1)3-3)2= | | 7.083333333=x^2-3x+6.75 | | 7.5(x-4)=-0.5x+34 | | x^2-(m+3)x+11=0 | | 14-4(3x+1)-8+2x-2= | | 8*14*11= | | 6x+59=12x+11 | | 3x^2-9x+20.25=21.25 | | q+14=8q+56 | | (2x+3)(x-1)=18 | | q+14=8q+8*7 | | x+12+8x=30 | | 7n+39=11n-13 | | u+4=4u-8 | | (2x+3)(x+1)=18 | | c+2c-5-5c=7 | | 3(2m-3)=8(m+1) | | x^3+5x^2+7x+35= | | 1.2(4x-3.2)=2 | | 2x-4(x+2)=x(2x-1) | | (7x+3)=6 | | 6C(12)=48 | | (7x+3)= | | (4x-10x)-40+3=2(x-1) | | 5z-4z=48 | | 1x=2x-7 | | 2x-37=24 | | 3x^2-x=5 | | X=2x-7 | | 2x-3y=24 | | 6t-6=9t-36 | | k^2+4k-77=0 |